The farmers' depot architecture for a zero-agrowaste supply chain - Avenilla, Alanis M.; Flores, Juan Paolo (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Free movement of agricultural supply and reduction of operational expenses are needed to increase farmer profits and decrease consumer costs. This design research posits that a new architectural typology to simplify the agricultural trading supply chain and to close the agricultural waste loop will facilitate benefits for both farmers and consumers. Supply chains and built precedents were analyzed to derive an architectural program. Theoretical research on waste, recycling, and bioenergy were repurposed into spatial concepts. Findings were synthesized into a case study that can serve as a framework for future developments of the Department of Agriculture.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Zero-agrowaste supply chain